Dynamic Endothelial Stalk Cell–Matrix Interactions Regulate Angiogenic Sprout Diameter - Wang, William Y.; Jarman, Evan H.; Lin, Daphne; Baker, Brendon M. (Frontiers in Bioengineering and Biotechnology, 2021)
Angiogenesis is a complex, multicellular process that involves bidirectional interactions between extracellular matrix (ECM) and collectively invading endothelial cell (EC) sprouts that extend the microvasculature during development, wound healing, and disease processes. While many aspects of angiogenesis have been well studied, the relationship between endothelial sprout morphology and subsequent neovessel function remains relatively unknown. Here, we investigated how various soluble and physical matrix cues that regulate endothelial sprouting speed and proliferation correspond to changes in sprout morphology, namely, sprout stalk diameter. We found that sprout stalk cells utilize a combination of cytoskeletal forces and proteolysis to physically compact and degrade the surrounding matrix, thus creating sufficient space in three-dimensional (3D) ECM for lateral expansion. As increasing sprout diameter precedes lumenization to generate perfusable neovessels, this work highlights how dynamic endothelial stalk cell–ECM interactions promote the generation of functional neovessels during sprouting angiogenesis to provide insight into the design of vascularized, implantable biomaterials.